2013
DOI: 10.1074/jbc.m113.455832
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Regulates Nuclear Factor I Dephosphorylation and Activity in Malignant Glioma Cell Lines

Abstract: Background: Nuclear factor I (NFI) phosphorylation controls the expression of glial genes associated with migration. Results: NFI is dephosphorylated and activated by a cleaved form of calcineurin in malignant glioma cells. Conclusion: NFI transcriptional activity in malignant glioma is regulated in part by calcineurin. Significance: Regulation of NFI by calcineurin provides a novel approach to control the expression of genes associated with migration/infiltration in malignant glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 81 publications
(111 reference statements)
0
18
0
Order By: Relevance
“…The B1 regulatory subunit of calcineurin, Ppp3r1 , was a gCIS in our screen and the catalytic subunit Ppp3ca was insertionally mutated in two tumors as well ( Table S2 ). Recently, the catalytic subunit of calcineurin was shown by IHC to be expressed in regions of high infiltration/migration in human GBMs [45] , however microarray data indicate that PPP3R1 ( Table 4 ) and PPP3CA (not shown) are under-expressed in human GBM compared to normal brain. Therefore further experiments will be necessary to characterize the contribution of calcineurin to gliomagenesis.…”
Section: Discussionmentioning
confidence: 97%
“…The B1 regulatory subunit of calcineurin, Ppp3r1 , was a gCIS in our screen and the catalytic subunit Ppp3ca was insertionally mutated in two tumors as well ( Table S2 ). Recently, the catalytic subunit of calcineurin was shown by IHC to be expressed in regions of high infiltration/migration in human GBMs [45] , however microarray data indicate that PPP3R1 ( Table 4 ) and PPP3CA (not shown) are under-expressed in human GBM compared to normal brain. Therefore further experiments will be necessary to characterize the contribution of calcineurin to gliomagenesis.…”
Section: Discussionmentioning
confidence: 97%
“…In MG, NFI regulates FABP7, the expression of which coincides with increased tumor cell migration, tumor infiltration, and worse clinical prognosis (10,12,13,44). In the context of MG cells, NFI transcriptional activity is regulated by its phosphorylation state (45), with dephosphorylation of NFI mediated by the calcineurin phosphatase, a well-known target of calpain (21,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the importance of NFI phosphorylation state for calpastatin subcellular localization, we treated U251 MG cells with 1 M cyclosporin A (CSA), an inhibitor of calcineurin that promotes NFI hyperphosphorylation (21). CSA-treated U251 MG cells showed increased levels of hyperphosphorylated NFI (indicated by the asterisks) (Fig.…”
Section: Cast Gene Regulation In Glioblastoma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported the alteration of striatal dopaminergic function in glioma development ( 30 ). Furthermore, dysregulation of serine/threonine phosphatase calcineurin has also been reported in grade IV astrocytoma tumor tissue ( 31 ). The enrichment analysis results further confirmed the effects of the dysregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%